Tingkat Pengembangan Dan Daya Terima Bolu Kukus Berbahan Dasar Tepung Singkong (Manihot Esculenta Crantz) Yang Disubstitusi Tepung Daun Katuk (Sauropus Androgynus) - Indri Hapsari, Putri, Eni Purwani, S.Si., M.Si, Rusdin Rauf, S.TP., M.P (2015)
Background: The cassava and katuk leaves can be processed into flour through drying and refining and also can be used as raw materials in substituting wheat flour. The cassava flour and katuk leaves flour substitution in making steamed spongecake can reducing the people demand of wheat flour, so it can be consumed by all people. Purpose: The purpose of the research was to evaluate development level and consumer acceptance steamed spongecake of basic cassava flour in substitution katuk leaves flour. Research Method: This research used complete random design with four different sampling ratio of katuk leaves flour, which is 0%, 2,5%, 5% and 7,5%. Data were analyzed of steamed spongecake development and consumer acceptance using statistic test method One Way Anova and continued with Duncan Multiple Range Test (DMRT) with 95% significant ratio. Result: The result indicated that steamed spongecake development was affected by the substitution of katuk leaves flour. 0% and 2,5% ratio of katuk leaves flour substitute have a great result and have a good steamed spongecake development. Steamed spongecake with 2,5% ratio of katuk leaves flour substitute were the most preferred by consumers. Conclusion: There is no effect of substitution wheat flour into katuk leaves flour on steamed spongecake development. There is an effect of substitution wheat flour into katuk leaves flour to the acceptability. Keywords: development level, consumer acceptance, steamed spongecake, cassava flour, katuk leaves flour. Bibliography: 42 (1985 - 2014)